1997
DOI: 10.1093/rheumatology/36.7.763
|View full text |Cite
|
Sign up to set email alerts
|

Ligase chain reaction in detection of Chlamydia DNA in synovial fluid cells.

Abstract: Synovial fluid cells from 12 patients with reactive arthritis (ReA) triggered by Chlamydia trachomatis were studied for the presence of Chlamydia DNA using the ligase chain reaction (LCR) LCx (Abbott) and the polymerase chain reaction (PCR) Amplicor (Roche). In addition, peripheral blood leucocytes from 11 of these patients were analysed by LCR. As controls, seven patients with newly diagnosed rheumatoid arthritis (RA) were included. Chlamydia trachomatis DNA was detectable by LCR in samples of synovial fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
(28 reference statements)
0
4
0
2
Order By: Relevance
“…Although Borrelia species grow in the laboratory, they have seldom been cultured from joint specimens. The same is true in cases of venereal arthritis triggered by Chlamydia trachomatis 14 or Neisseria gonorrhoeae 15. In these situations PCR with species specific primers has proved to be a useful complementary tool to obtain the final diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Although Borrelia species grow in the laboratory, they have seldom been cultured from joint specimens. The same is true in cases of venereal arthritis triggered by Chlamydia trachomatis 14 or Neisseria gonorrhoeae 15. In these situations PCR with species specific primers has proved to be a useful complementary tool to obtain the final diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Chlamydia trachomatis is the most common bacterial factor transmitted sexually that causes SARA reactive arthritis. These bacteria are detected in both the genitourinary system and the synovial fluid, synovial membrane and synovial tissue [ 1 , 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have detected chlamydia in the synovial fluid, synovial membrane or synovial tissue [ 5 , 8 , 10 , 14 16 ]. Nikkari et al [ 10 ] observed C. trachomatis DNA in synovial fluid in 33.3% of patients with ReA. Taylor-Robinson et al [ 14 ] detected chlamydia in the synovial fluid and synovial membrane in ReA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse mesmo estudo, os autores obtiveram apenas dois resultados positivos para o DNA clamidial em 79 pacientes com EI (2,5%). Contudo, Nikkari et al (32) , empregando a mesma técnica de DNA, não encontraram nenhuma amostra positiva para C. trachomatis no líquido sinovial de 12 pacientes com ARe. Esse resultado está de acordo com o de outros estudos, como o de Wordsworth et al (20) , que também não detectaram o DNA plasmidial, empregando PCR desenvolvida pelos autores, em nove articulações de pacientes com ARe. Alguns pesquisadores que realizaram PCR no líquido sinovial, tendo como alvo o DNA da MOMP, também não obtiveram resultado positivo em pacientes com Are (21,29) .…”
Section: Discussionunclassified
“…Ximenes (48) , em um estudo com 40 pacientes com Are, detectaram anticorpos IgG anti-C. trachomatis em 34,7% e IgM em 13,0%. Nikkari et al (32) (42) , não foi possível estabelecer correlação entre a presença de anticorpos e a detecção do DNA, em razão do pequeno número de pacientes com PCR positiva.…”
Section: Discussionunclassified